Online learning for university students on the autism spectrum: A systematic review and questionnaire study - Adams, Dawn; Simpson, Kate; Davies, Lynda; Campbell, Chris; Macdonald, Libby (Australasian Journal of Educational Technology, 2019)
Online course delivery is increasingly being used by universities to deliver accessible and flexible learning environments. As this mode of delivery grows it is important to consider the equity of the learning experience for all students. As online delivery may reduce challenges and stressors present in face-to-face delivery, it could be suggested that it may promote student learning for specific student groups, including those with a diagnosis on the autism spectrum. However, little is known about the experience of learning online for students on the autism spectrum. This paper presents findings from two studies: A systematic review of the literature and a survey of students on the autism spectrum studying online. From the systematic literature review, only four previous studies were identified reporting on this topic. Findings from two studies identified that the online environment provided both facilitators and barriers to the learning experience for students on the autism spectrum. Although the online environment provided flexibility for learning, how design factors are employed in online delivery may unintentionally create barriers to the learning experience for students on the spectrum. An outcome from this study has been the creation of a suite of resources to assist with course design and delivery.